2015
DOI: 10.1016/j.jval.2015.09.2077
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Illness Study of Type 2 Diabetes Mellitus in the Newly Established Diabetology Outpatient Facility in the Czech Republic

Abstract: A603tion of all direct costs we determined that the total average cost of uncomplicated hypothyroidism during pregnancy and childbed per women was € 124.79. In the cost structure of health care provision for pregnant women with uncomplicated hypothyroidism the most significant costs are spent on thyroid laboratory tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
2
Order By: Relevance
“…All costs are reported in mean and standard deviation for normally distributed variables and median and IQR for not normally distributed variables. In our study, the overall median cost of treatment was found to be 295.6 $ as compared with 444.62 $ reported by Gajdos et al in the Czech Republic, 26 1912 $ by Malone et al in Australia, 27 118.8 $ by Eshwari et al in India 28…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…All costs are reported in mean and standard deviation for normally distributed variables and median and IQR for not normally distributed variables. In our study, the overall median cost of treatment was found to be 295.6 $ as compared with 444.62 $ reported by Gajdos et al in the Czech Republic, 26 1912 $ by Malone et al in Australia, 27 118.8 $ by Eshwari et al in India 28…”
Section: Resultscontrasting
confidence: 44%
“…All costs are reported in mean and standard deviation for normally distributed variables and median and IQR for not normally distributed variables. In our study, the overall median cost of treatment was found to be 295.6 $ as compared with 444.62 $ reported by Gajdos et al in the Czech Republic, 26 1912 $ by Malone et al in Australia, 27 118.8 $ by Eshwari et al in India. 28 In our study, diagnostic tests' cost in patients with DM and HTN was found to be 14.8 $ compared with 7.71 $ reported by Agrawal et al in India 29 and 24.31$ reported by Moucheraud et al in India 30 .…”
Section: Re Sultscontrasting
confidence: 48%
“…Differences in life expectancy can be explained by many risk factors that are both specific to each disease, on the other hand, many diseases are affected by the same risk factors, like chronic diseases (2)(3)(4). Non-communicable diseases are responsible for nearly two thirds of all deaths (in Slovakia recently even more) and exhibit about 50% of global burden diseases (5).…”
Section: Introductionmentioning
confidence: 99%
“…There are many similar research studies (3,(5)(6)(7)(8), their importance results from the detection of context and regional disparities in mortality in specific groups of diseases, in order to subsequently detect all determinants that cause these disparities and thus contribute to the deepening of inequalities in health between regions and between countries. European Union programs clearly put pressure to eliminate these inequalities in health and to the development of active policies and international benchmarks that would support improving the health of populations worldwide (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%